Polarity-Switchable Symmetric Graphite Batteries with High Energy and High Power Densities - Wang, Gang (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.